A microwave-absorbing boron nitride fiber with adjustable dielectric properties and a preparation method thereof

By preparing a multi-layer composite structure on boron nitride fibers, and using activation treatment and multi-step chemical treatment methods, the problem of the inability to adjust the dielectric properties of boron nitride fibers in the prior art is solved, cross-order of magnitude adjustment of dielectric properties and the improvement of electromagnetic wave absorption and reflection functions, expanding its application fields.

CN119372808BActive Publication Date: 2025-03-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411923205.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Existing high-temperature electromagnetic wave absorbing materials are easy to "display" under radar detection, and boron nitride fibers cannot effectively adjust their dielectric properties and cannot meet the needs of different applications.

Method used

Using activation treatment, melt spinning, partial oxidation treatment, partial nitriding/carbonization treatment and post-treatment, wave absorbing boron nitride fibers with adjustable dielectric properties with multi-layer composite structures were prepared. The fiber consists of a wave-transmitting layer, an absorbing layer and a reflective layer. Through the component design and thickness adjustment of each layer, the dielectric performance can be adjusted across orders of magnitude.

Benefits of technology

It effectively avoids the problems of poor bonding performance between the surface coating and the carrier fiber in traditional absorbing materials, easy layering and impedance mismatch, and achieves good electromagnetic wave absorption and reflection functions of boron nitride fibers, and meets the diversified needs of different dielectric properties, expanding the application field of boron nitride fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372808B_ABST
    Figure CN119372808B_ABST
Patent Text Reader

Abstract

The present invention provides an absorbing boron nitride fiber with adjustable dielectric properties and a preparation method thereof, belonging to the field of absorbing boron nitride fibers. The preparation method of the absorbing boron nitride fiber with adjustable dielectric properties consists of the following steps: activation treatment, melt spinning, partial oxidation treatment, partial nitridation / carbonization treatment, and post-treatment. The absorbing boron nitride fiber with adjustable dielectric properties and a preparation method thereof of the present invention can effectively avoid the defects of poor bonding performance between the surface coating and the carrier fiber, easy stratification, impedance mismatch, and uneven thickness of the surface coating in traditional absorbing materials; while enabling the boron nitride fiber to have good electromagnetic wave absorption and reflection functions, it can achieve cross-order-of-magnitude regulation of dielectric properties, effectively meet the diversified needs for boron nitride fibers with different dielectric properties in the application field of electromagnetic absorbing materials, and further expand the application field of boron nitride fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of wave-absorbing boron nitride fibers, and in particular to a wave-absorbing boron nitride fiber with adjustable dielectric properties and a preparation method thereof. Background Art

[0002] In the prior art, high-temperature electromagnetic absorbing materials usually need to meet the following two requirements: on the one hand, the surface of the material in contact with the outside world should have a suitable interface impedance, so that most electromagnetic waves can pass through the material surface without reflection, that is, the material surface has a certain electromagnetic permeability; on the other hand, the material should have a good electromagnetic wave loss capacity inside, fully absorbing the electromagnetic waves that pass through without reflection. Therefore, the former usually requires the material to have a higher resistivity and a lower real part of the dielectric constant, while the latter usually requires the material to have a low resistivity and a high imaginary part of the dielectric constant.

[0003] Existing high-temperature electromagnetic absorbing materials usually use absorbing materials (such as silicon carbide fiber, carbon fiber, etc.) as carriers, and generate a wave-transmitting layer on their surface to achieve the purpose of functional composite. Based on this, the commonly used preparation methods include: precursor impregnation pyrolysis method, chemical vapor deposition method, etc.; but the wave-transmitting coating coated on the surface of the absorbing material carrier fiber has defects such as uneven thickness, poor bonding performance between the wave-transmitting coating and the carrier fiber, and easy delamination. At the same time, due to the large difference in impedance between the wave-transmitting coating and the carrier fiber (usually 10 6 Up to 10 8 There is also an impedance mismatch problem between the wave-transmitting coating and the absorbing material, which causes the scattering and refraction of electromagnetic waves between their layers, resulting in the inability to completely absorb the electromagnetic waves, causing the high-temperature electromagnetic absorbing material to "show up" under radar detection.

[0004] Boron nitride fiber is a polycrystalline fiber with boron nitride as the main component. It has the characteristics of high temperature resistance, good stability, excellent dielectric properties (such as low dielectric constant, low dielectric loss), good wave transmission performance, etc. It is mainly used in ceramic matrix composite materials, ultra-high-speed aircraft and other fields. Boron nitride fiber, as a typical wave-transmitting fiber, has the characteristics of low dielectric constant and low dielectric loss, and its absorption and reflection ability of electromagnetic waves is poor; due to the wide application of boron nitride fiber in wave transmission, the existing boron nitride fiber preparation method usually focuses on improving the density of boron nitride fiber by reducing impurities (such as carbon, oxygen impurities, etc.) and defects in boron nitride fiber, thereby improving the dielectric wave transmission performance of boron nitride fiber; however, it is impossible to transform boron nitride fiber from a single electromagnetic wave transmission characteristic to a functional absorbing material with good electromagnetic wave absorption and reflection functions.

[0005] Furthermore, in the aforementioned existing boron nitride fiber preparation process, in order to reduce impurities (such as carbon, oxygen impurities, etc.) and defects in the boron nitride fiber, it is necessary to treat the fiber at high temperature in a single high-purity atmosphere (such as oxygen, ammonia, nitrogen, etc.) environment, thereby completely transforming the components and structure in the boron nitride fiber to achieve the purpose of removing impurities and reducing defects. The dielectric properties of the boron nitride fiber cannot be effectively adjusted, and it is impossible to achieve cross-order-of-magnitude adjustment of the dielectric properties while the boron nitride fiber has good electromagnetic wave absorption and reflection functions, and thus it is impossible to meet the diversified needs of boron nitride fibers with different dielectric properties in the application field of electromagnetic wave absorbing materials, limiting the further expansion of the application field of boron nitride fibers. Summary of the invention

[0006] In order to solve the technical problems existing in the prior art, the present invention provides a wave-absorbing boron nitride fiber with adjustable dielectric properties and a preparation method thereof, which can effectively avoid the defects of poor bonding performance between the surface coating and the carrier fiber, easy delamination, impedance mismatch, and uneven thickness of the surface coating in traditional wave-absorbing materials; it can enable the boron nitride fiber to have good electromagnetic wave absorption and reflection functions while realizing cross-order-of-magnitude adjustment of the dielectric properties, effectively meeting the diversified needs for boron nitride fibers with different dielectric properties in the application field of electromagnetic wave-absorbing materials, and further expanding the application field of boron nitride fibers.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a wave-absorbing boron nitride fiber with adjustable dielectric properties, comprising the following steps: activation treatment, melt spinning, partial oxidation treatment, partial nitridation / carbonization treatment, and post-treatment;

[0009] The activation treatment method comprises dissolving a polyborazane precursor and a polysilazane precursor in a solvent to obtain a mixed precursor solution; subjecting the mixed precursor solution to ultrasonic treatment; while subjecting the mixed precursor solution to ultrasonic treatment, continuously introducing boron trichloride gas below the liquid surface of the mixed precursor solution to obtain an activation treatment solution; and removing the solvent from the activation treatment solution to obtain a solid multiphase precursor A.

[0010] The melt spinning method comprises: performing melt spinning on a solid multiphase precursor A to obtain a multiphase precursor fiber B;

[0011] The partial oxidation treatment method is to control the reaction atmosphere to be dry air, and to heat-treat the composite precursor fiber B at a temperature of 90-160° C. to obtain a partially oxidized fiber C;

[0012] The method of partial nitridation / carbonization treatment is to control the reaction atmosphere to be a mixture of ammonia and nitrogen, and to heat-treat the partially oxidized fiber C at a temperature of 400-600° C. to obtain a partially nitrided / carbonized fiber D;

[0013] The post-treatment method is to control the reaction atmosphere to be nitrogen, and to subject the partially nitrided / carbonized fiber D to heat treatment to obtain a wave-absorbing boron nitride fiber with adjustable dielectric properties.

[0014] Preferably, in the activation treatment, the mass ratio of the polyborazane precursor to the polysilazane precursor is 70-97:3-30;

[0015] The volume of the solvent is at least 3 times the total volume of the polyborazine precursor and the polysilazane precursor.

[0016] Preferably, in the activation treatment, the ultrasonic frequency is 20-25kHz, the ultrasonic power is 450-550W, and the water bath ultrasonic temperature is 50-60°C;

[0017] The introduction rate of boron trichloride gas is 0.5-0.6L / min;

[0018] The time for ultrasonic treatment and passing boron trichloride gas is 10-30 minutes.

[0019] Preferably, in the activation treatment, the polymer dispersibility index PDI of the solid multiphase precursor A obtained is between 2.2 and 4.3.

[0020] Preferably, in the melt spinning, the average diameter of the complex phase precursor fiber B is 16-20 μm.

[0021] Preferably, the partial oxidation treatment is heated to 90-160°C at a heating rate of 1-10°C / min;

[0022] The 90-160℃ insulation treatment time is 10-60min.

[0023] Preferably, in the partial nitriding / carbonizing treatment, the heating rate to 400-600°C is 1-10°C / min;

[0024] The heat preservation time at 400-600℃ is 10-60min;

[0025] The volume ratio of ammonia to nitrogen is 1:5-20.

[0026] Preferably, in the post-treatment, the heat treatment temperature is 1200°C;

[0027] The heating rate to 1200°C is 1-10°C / min;

[0028] The 1200℃ insulation treatment time is 10-60min.

[0029] A wave-absorbing boron nitride fiber with adjustable dielectric properties is prepared by the above-mentioned preparation method; the wave-absorbing boron nitride fiber with adjustable dielectric properties comprises, from outside to inside, a wave-transmitting layer, a wave-absorbing layer, and a reflecting layer.

[0030] Furthermore, the relative dielectric constant of the wave-absorbing boron nitride fiber with adjustable dielectric properties is 3.5-7.5, and the dielectric loss is 9×10 -3 to 6.5×10 -2 .

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The method for preparing absorbing boron nitride fiber with adjustable dielectric properties of the present invention is aimed at the current situation that the existing absorbing ceramic fiber needs to be coated with an additional interface layer before use to meet the use requirements. It also aims at the defects that the added physical adsorption bonding coating has poor bonding performance with the carrier fiber, is easy to delaminate, and has uneven thickness of the surface coating. The absorbing boron nitride fiber is used as the matrix, and a absorbing layer, a transition absorbing layer and a reflecting layer are generated in situ during the preparation process. The layers are chemically bonded to each other and have strong bonding performance. At the same time, since the components of the layers are similar, they will not fall off due to expansion and deformation during actual use. No additional coating operation is required, and one fiber (i.e., the absorbing boron nitride fiber of the present invention) can be directly used as an absorbing material.

[0033] (2) The method for preparing absorbing boron nitride fiber with adjustable dielectric properties of the present invention obtains absorbing boron nitride fiber with a multi-layer composite structure through the process of activation treatment, partial oxidation treatment, partial nitridation / carbonization treatment and post-treatment. By designing the components of each functional layer from the outside to the inside and adjusting the thickness of each functional layer, the functional layers are tightly combined and there is an obvious transition in the component structure of each functional layer, which effectively solves the impedance mismatch problem between the wave-transmitting layer and the wave-absorbing layer; the electromagnetic wave absorption characteristics of the boron nitride fiber can be controlled and adjusted; at the same time, through the above-mentioned preparation method, each functional layer is generated in situ, the interlayer bonding performance is good, and no falling off or stratification will occur.

[0034] (3) The method for preparing a wave-absorbing boron nitride fiber with adjustable dielectric properties of the present invention comprises a wave-absorbing boron nitride fiber with adjustable dielectric properties, which comprises, from the outside to the inside, a wave-transmitting layer, a wave-absorbing layer, and a reflective layer. Taking the multiphase precursor fiber B prepared by melt spinning with an average diameter of 16 μm as an example, the wave-transmitting layer thickness of the finally prepared wave-absorbing boron nitride fiber is 0.5-4 μm, the wave-absorbing layer thickness is 0.5-2.5 μm, and the reflective layer thickness is 1-4 μm. The relative dielectric constant of the wave-absorbing boron nitride fiber is 3.5-7.5, and the dielectric loss is 9×10 -3 to 6.5×10-2 It can make the boron nitride fiber have good electromagnetic wave absorption and reflection functions, and at the same time realize cross-order-of-magnitude adjustment of dielectric properties, effectively meet the diversified needs of boron nitride fibers with different dielectric properties in the application field of electromagnetic absorbing materials, and further expand the application field of boron nitride fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The dielectric loss curve of the absorbing boron nitride fiber with adjustable dielectric properties of the present invention is shown in FIG. In the figure, the upper curve is the dielectric loss curve of the absorbing boron nitride fiber of the present invention, and the lower curve is the dielectric loss curve of the conventional boron nitride fiber in the prior art.

[0036] Figure 2 This is a microscopic morphology of the microwave-absorbing boron nitride fiber with adjustable dielectric properties of Example 2.

[0037] Figure 3 This is a distribution curve of the carbon content in the microwave-absorbing boron nitride fiber with adjustable dielectric properties in Example 2 along the radial direction (from the center to the outer layer). DETAILED DESCRIPTION

[0038] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0039] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific embodiments of the present invention are now described. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those of ordinary skill in the art to which the present invention belongs.

[0040] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, "first", "second", etc. are used to distinguish similar objects, and are not used to describe a specific order or sequence. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0041] An embodiment of the present invention provides a method for preparing a wave-absorbing boron nitride fiber with adjustable dielectric properties. The wave-absorbing boron nitride fiber is a nitride fiber with boron nitride as the main phase and is doped with 3-30wt% of polysilazane (PSZ).

[0042] The method for preparing the wave-absorbing boron nitride fiber with adjustable dielectric properties comprises the following steps: activation treatment, melt spinning, partial oxidation treatment, partial nitridation / carbonization treatment, and post-treatment.

[0043] The activation treatment method comprises the following steps: adding a polyborazine precursor and a polysilazane precursor having similar softening points into a toluene solvent, stirring and dissolving the two precursors, and obtaining a mixed precursor solution after the two precursors are completely dissolved in the toluene solvent; placing the mixed precursor solution in a water bath ultrasonic device, controlling the ultrasonic frequency to be 20-25 kHz, the ultrasonic power to be 450-550 W, and the water bath ultrasonic temperature to be 50-60° C., and performing water bath ultrasonic treatment; while performing the water bath ultrasonic treatment, inserting a molten-liquid into the mixed precursor solution to obtain a mixed precursor solution; The high-purity boron trichloride gas is continuously introduced through a ventilation pipe below the surface, and the introduction rate of the high-purity boron trichloride gas is controlled to be 0.5-0.6L / min; after water bath ultrasonic treatment and continuous introduction of high-purity boron trichloride gas for 10-30min, an activated treatment liquid is obtained; then, in an inert atmosphere (nitrogen, etc.), the solvent is removed to obtain a solid multiphase precursor A with a wide molecular weight distribution; the molecular weight of the solid multiphase precursor A and the polymer dispersity index PDI in the distribution curve are between 2.2 and 4.3.

[0044] In the activation treatment, a silicon-containing component is introduced into the precursor component design by doping a polysilazane precursor to meet the subsequent functional design requirements; the two precursors are uniformly dispersed in a toluene solvent due to their similar softening points and molecular weights to obtain a mixed precursor solution; then water bath ultrasonic treatment and boron trichloride gas activation are simultaneously performed to produce more small molecules in the multiphase precursor, and combined with the subsequent solvent removal operation, the small molecules can be stably retained in the solid multiphase precursor A.

[0045] In the activation treatment, the polyborazane precursor is a six-membered cyclic polymer with a certain molecular weight, a high degree of molecular chain cyclization, and a very low amount of small molecule residues; in the solution state, the present invention, under a certain temperature and ultrasonic vibration, combined with the introduction of boron trichloride gas, can promote the partial dissociation of the six-membered ring of polyborazane into a short chain structure, and make the precursor converted into a small molecular weight retained in the mixed solution, and finally prepare a solid multiphase precursor A with a wide molecular weight distribution. The above operation can retain the small molecules retained in the mixed precursor to the greatest extent, and the retained small molecules play a pore-forming role in subsequent treatment, and the dielectric properties of the boron nitride fiber are regulated by the fiber pores.

[0046] In the activation treatment, toluene is used to provide a solvent environment, and the activation treatment conditions for the polyborazane precursor and the polysilazane precursor are mild, which can achieve molecular-level mixing and activation of the two precursors, effectively avoiding the adverse effects on the spinnability of the prepared solid-state composite precursor A during the mixing and activation of the two precursors, avoiding fluctuations in its spinnability, and improving batch stability.

[0047] The mass ratio of the polyborazane precursor to the polysilazane precursor is preferably 70-97:3-30; more preferably 70-90:10-30.

[0048] The volume amount of the toluene solvent is preferably at least 3 times the total volume of the polyborazane precursor and the polysilazane precursor.

[0049] The melt spinning method is to place a solid multiphase precursor A in a melt spinning device, and obtain multiphase precursor fibers B with an average diameter of 16-20 μm through melt spinning.

[0050] The partial oxidation treatment method is to place the complex phase precursor fiber B in an atmosphere sintering furnace, control the reaction atmosphere to be dry air, heat it to 90-160°C at a heating rate of 1-10°C / min, and keep it warm for 10-60 minutes to obtain partially oxidized fiber C.

[0051] In the partial oxidation treatment, dry air atmosphere and temperature process control are key factors for causing partial surface oxygen cross-linking of the complex precursor fiber B, thereby forming a cross-linked layer with controllable thickness; specifically, oxidation in a certain thickness area on the fiber surface produces BNO and SiNO components, and the inner layer of the fiber is controlled not to react, thereby achieving partial oxidation of the outer layer of the fiber.

[0052] The method of partial nitridation / carbonization treatment is as follows: after preparing partially oxidized fiber C, the reaction atmosphere is controlled to be a mixture of ammonia and nitrogen, the temperature is increased to 400-600°C at a heating rate of 1-10°C / min, and the temperature is kept for 10-60 minutes to obtain partially nitrided / carbonized fiber D.

[0053] In the partial nitridation / carbonization treatment, the reaction atmosphere and temperature process control are key factors for fiber nitridation and carbon fixation, thereby forming a transition layer with controllable thickness. In this process, the cross-linked layer on the surface of the partially oxidized fiber C is only nitrided and converted into a composite fiber "skin" in which BN, BNO and SiNO coexist; while the nitridation and carbonization of the intermediate layer of the partially oxidized fiber C are carried out simultaneously, forming a composite fiber transition layer with BN, Si3N4 and carbon as the complex phase.

[0054] The volume ratio of ammonia to nitrogen is preferably 1:5-20.

[0055] The post-treatment method is to prepare partially nitrided / carbonized fiber D, control the reaction atmosphere to be nitrogen, heat it to 1200°C at a heating rate of 1-10°C / min, and keep it warm for 10-60min to obtain a boron nitride fiber with a multi-layer composite structure, i.e., a wave-absorbing boron nitride fiber.

[0056] In the post-treatment, the reaction atmosphere and temperature process control are key factors in forming the final multiphase structure; the nitrogen atmosphere can maintain the transition layer of Si3N4 and carbon formed in the previous steps without decomposition, and the temperature process control can promote the decomposition of BNO and SiNO in the fiber surface cross-linking layer to generate B2O3 and SiO gaseous products, leaving only BN as a wave-transmitting layer; at the same time, the inner layer of the fiber solidifies to form a stable structure and does not decompose, and is converted into a reflection layer mainly composed of amorphous carbon, and the middle layer is a transition layer with BN, Si3N4 and carbon coexisting in a certain proportion. The present invention realizes the controllable change of the impedance of the wave-absorbing boron nitride fiber by controllable preparation and continuous transition of the thickness of each functional layer mentioned above.

[0057] Furthermore, during the post-treatment process, BNO and SiNO in the aforementioned cross-linked layer decompose to generate gaseous products of B2O3 and SiO, and the dissipation of the gaseous products will cause more through-hole structures on the fiber surface; at the same time, the small molecules introduced during the precursor mixing process will also rapidly evaporate in this process to form a uniformly distributed through-hole structure; the existence of the aforementioned through-hole structure, on the one hand, is conducive to the further contact reaction between the reaction atmosphere and the interior of the fiber, and more importantly, when the electromagnetic wave is incident on the fiber pores, due to the large specific surface area of ​​the abundant pores, the electromagnetic wave is continuously reflected / diffusely reflected / refracted in the pores, which will also produce energy attenuation to a certain extent, causing an increase in dielectric loss, thereby improving the wave absorption performance of the boron nitride fiber.

[0058] In the aforementioned partial oxidation treatment, partial nitridation / carbonization treatment, and post-treatment process, the generation and thickness of each functional layer in the fiber are regulated by controlling the different reaction atmospheres and temperature processes in each step, especially by controlling the time of the heat preservation treatment; different functional layer thicknesses are generated correspondingly by different treatment conditions, so that the absorbing boron nitride fiber exhibits different dielectric properties, thereby achieving the purpose of adjustable dielectric properties.

[0059] The method for preparing the wave-absorbing boron nitride fiber with adjustable dielectric properties of the present invention is different from the improvement direction of reducing impurities and defects in the fiber as much as possible and improving the density of the fiber in the preparation of the existing wave-transmitting boron nitride fiber. Instead, it uses the component impurities and hole defects of the fiber through a specific preparation method to achieve the regulation of the dielectric properties of the boron nitride fiber. In the preparation process, it tends to artificially and controllably generate new beneficial defects, and retain the beneficial impurities and beneficial defects in the fiber (the "beneficial" mentioned here means that it is beneficial to improve the wave-absorbing performance of the boron nitride fiber and to regulate the dielectric properties of the boron nitride fiber).

[0060] The embodiment of the present invention also provides a wave-absorbing boron nitride fiber prepared by the above method, which comprises, from the outside to the inside, a wave-transmitting layer, a wave-absorbing layer, and a reflecting layer; the wave-absorbing boron nitride fiber has a relative dielectric constant of 3.5-7.5 and a dielectric loss of 9×10 -3 to 6.5×10-2 .

[0061] The dielectric absorbing boron nitride fiber of the present invention is prepared by combining the above-mentioned specific preparation methods to obtain a fiber structure having a wave-transmitting layer, a wave-absorbing layer and a reflective layer, wherein the outermost layer is a porous BN layer (wave-transmitting layer) having the highest resistivity, which plays a role in impedance matching with the outside air and electromagnetic wave transmission; the middle transition layer is a BN / Si3N4 / C layer (wave-absorbing layer), whose resistivity is lower than that of the outermost layer, which plays a role in impedance matching transition with the upper layer (wave-transmitting layer) and electromagnetic wave absorption; the inner layer is a carbon layer (reflective layer), which has the lowest resistivity and plays a role in reflecting electromagnetic waves; the above-mentioned technical means cooperate and work synergistically with each other, which can effectively avoid the defects of poor bonding performance between the surface coating and the carrier fiber, easy delamination, impedance mismatch, and uneven thickness of the surface coating in traditional wave-absorbing materials; the boron nitride fiber can have good electromagnetic wave absorption and reflection functions, while realizing cross-order-of-magnitude adjustment of dielectric properties, effectively meeting the diversified needs for boron nitride fibers with different dielectric properties in the application field of electromagnetic wave absorbing materials, and further expanding the application field of boron nitride fibers.

[0062] The present invention is further described below in conjunction with some specific embodiments.

[0063] Example 1

[0064] This embodiment provides a method for preparing a microwave-absorbing boron nitride fiber with adjustable dielectric properties, specifically:

[0065] 1. Activation treatment

[0066] A polyborazane precursor and a polysilazane precursor are put into a toluene solvent, stirred and dissolved, and the two precursors are completely dissolved in the toluene solvent to obtain a mixed precursor solution; the mixed precursor solution is placed in a water bath ultrasonic device, and the ultrasonic frequency is controlled to be 20kHz, the ultrasonic power is controlled to be 480W, and the water bath ultrasonic temperature is controlled to be 50°C, and water bath ultrasonic treatment is performed; while the water bath ultrasonic treatment is performed, high-purity boron trichloride gas is continuously introduced through a vent pipe inserted below the liquid surface of the mixed precursor solution, and the introduction rate of the high-purity boron trichloride gas is controlled to be 0.5L / min; after the water bath ultrasonic treatment and the continuous introduction of the high-purity boron trichloride gas for 10 minutes, an activated treatment liquid is obtained; then, the solvent is removed in an inert atmosphere (nitrogen, etc.) environment to obtain a solid multiphase precursor A with a wide molecular weight distribution; the polymer dispersity index PDI of the solid multiphase precursor A is 4.22.

[0067] The mass ratio of the polyborazane precursor to the polysilazane precursor is 70:30.

[0068] The volume amount of toluene solvent used is 3 times the total volume of the polyborazine precursor and the polysilazane precursor.

[0069] 2. Melt spinning

[0070] The solid multiphase precursor A is placed in a melt spinning device, and multiphase precursor fibers B with an average diameter of 16 μm are obtained through melt spinning.

[0071] 3. Partial oxidation treatment

[0072] The composite precursor fiber B was placed in an atmosphere sintering furnace, the reaction atmosphere was controlled to be dry air, the temperature was increased to 160°C at a heating rate of 2°C / min, and the temperature was kept for 60 minutes to obtain partially oxidized fiber C.

[0073] 4. Partial nitriding / carburizing treatment

[0074] After partially oxidized fiber C was prepared, the reaction atmosphere was controlled to be a mixture of ammonia and nitrogen, and the temperature was continued to be increased to 500° C. at a heating rate of 2° C. / min and kept at this temperature for 30 minutes to obtain partially nitrided / carbonized fiber D.

[0075] Among them, the volume ratio of ammonia to nitrogen is 1:20.

[0076] 5. Post-processing

[0077] After partially nitrided / carbonized fiber D was prepared, the reaction atmosphere was controlled to be nitrogen, the temperature was raised to 1200°C at a heating rate of 2°C / min, and the temperature was kept for 30 minutes to obtain a boron nitride fiber with a multilayer composite structure, namely, an absorbing boron nitride fiber.

[0078] The present embodiment also provides a wave-absorbing boron nitride fiber prepared by the above method, which comprises, from outside to inside, a wave-transmitting layer, a wave-absorbing layer, and a reflecting layer; the wave-transmitting layer has a thickness of 4 μm; the wave-absorbing layer has a thickness of 0.5 μm, and the reflecting layer has a thickness of 1 μm; the wave-absorbing boron nitride fiber has a relative dielectric constant of 5.1 and a dielectric loss of 9.35×10 -3 .

[0079] Example 2

[0080] This embodiment provides a method for preparing a microwave-absorbing boron nitride fiber with adjustable dielectric properties, specifically:

[0081] 1. Activation treatment

[0082] A polyborazane precursor and a polysilazane precursor are put into a toluene solvent, stirred and dissolved, and the two precursors are completely dissolved in the toluene solvent to obtain a mixed precursor solution; the mixed precursor solution is placed in a water bath ultrasonic device, and the ultrasonic frequency is controlled to be 22kHz, the ultrasonic power is 500W, and the water bath ultrasonic temperature is 60°C to perform water bath ultrasonic treatment; while performing the water bath ultrasonic treatment, high-purity boron trichloride gas is continuously introduced through a vent pipe inserted below the liquid surface of the mixed precursor solution, and the introduction rate of the high-purity boron trichloride gas is controlled to be 0.5L / min; after the water bath ultrasonic treatment and the continuous introduction of the high-purity boron trichloride gas for 20 minutes, an activated treatment solution is obtained; then, the solvent is removed in an inert atmosphere (nitrogen, etc.) environment to obtain a solid multiphase precursor A with a wide molecular weight distribution; the polymer dispersity index PDI of the solid multiphase precursor A is 3.34.

[0083] The mass ratio of the polyborazane precursor to the polysilazane precursor is 80:20.

[0084] The volume amount of toluene solvent used is 3 times the total volume of the polyborazine precursor and the polysilazane precursor.

[0085] 2. Melt spinning

[0086] The solid multiphase precursor A is placed in a melt spinning device, and multiphase precursor fibers B with an average diameter of 16 μm are obtained through melt spinning.

[0087] 3. Partial oxidation treatment

[0088] The composite precursor fiber B was placed in an atmosphere sintering furnace, the reaction atmosphere was controlled to be dry air, the temperature was increased to 120°C at a heating rate of 5°C / min, and the temperature was kept for 60 minutes to obtain partially oxidized fiber C.

[0089] 4. Partial nitriding / carburizing treatment

[0090] After partially oxidized fiber C was prepared, the reaction atmosphere was controlled to be a mixture of ammonia and nitrogen, the temperature was increased to 600° C. at a heating rate of 5° C. / min, and the temperature was kept for 60 minutes to obtain partially nitrided / carbonized fiber D.

[0091] Among them, the volume ratio of ammonia to nitrogen is 1:5.

[0092] 5. Post-processing

[0093] After partially nitrided / carbonized fiber D was prepared, the reaction atmosphere was controlled to be nitrogen, the temperature was raised to 1200°C at a heating rate of 5°C / min, and the temperature was kept for 60 minutes to obtain a boron nitride fiber with a multilayer composite structure, namely, an absorbing boron nitride fiber.

[0094] like Figure 2As shown, this embodiment also provides a wave-absorbing boron nitride fiber made by the above method, which includes, from outside to inside, a wave-transmitting layer, a wave-absorbing layer, and a reflecting layer; the wave-transmitting layer has a thickness of 2 μm; the wave-absorbing layer has a thickness of 2.5 μm, and the reflecting layer has a thickness of 1 μm; the wave-absorbing boron nitride fiber has a relative dielectric constant of 7.4 and a dielectric loss of 6.2×10 -2 .

[0095] Depend on Figure 2 The microscopic morphology of the fracture surface of the wave-absorbing boron nitride fiber in this embodiment can be clearly seen from its light and dark contrast that the wave-absorbing boron nitride fiber can be divided into three layers from the surface to the center, the outermost layer is darker in color, and the color becomes lighter toward the center; Figure 3 From the distribution curve of the carbon content of the fiber along the radial direction (from the center to the outer layer), it can be seen that the carbon content decreases gradually from the inside to the outside, showing an obvious layered distribution phenomenon, which indicates that through the preparation method of the dielectrically adjustable absorbing boron nitride fiber of this embodiment, the fiber can form a gradient-changing component and structure along the radial direction, corresponding to the three different functional layers (wave-transmitting layer, wave-absorbing layer, and reflective layer) mentioned above.

[0096] Example 3

[0097] This embodiment provides a method for preparing a microwave-absorbing boron nitride fiber with adjustable dielectric properties, specifically:

[0098] 1. Activation treatment

[0099] A polyborazane precursor and a polysilazane precursor are put into a toluene solvent, stirred and dissolved, and the two precursors are completely dissolved in the toluene solvent to obtain a mixed precursor solution; the mixed precursor solution is placed in a water bath ultrasonic device, and the ultrasonic frequency is controlled to be 20kHz, the ultrasonic power is controlled to be 480W, and the water bath ultrasonic temperature is controlled to be 55°C, and water bath ultrasonic treatment is performed; while the water bath ultrasonic treatment is performed, high-purity boron trichloride gas is continuously introduced through a vent pipe inserted below the liquid surface of the mixed precursor solution, and the introduction rate of the high-purity boron trichloride gas is controlled to be 0.6L / min; after the water bath ultrasonic treatment and the continuous introduction of the high-purity boron trichloride gas for 30 minutes, an activated treatment liquid is obtained; then, the solvent is removed in an inert atmosphere (nitrogen, etc.) environment to obtain a solid multiphase precursor A with a wide molecular weight distribution; the polymer dispersity index PDI of the solid multiphase precursor A is 2.22.

[0100] Wherein, the mass ratio of the polyborazane precursor to the polysilazane precursor is 90:10.

[0101] The volume amount of toluene solvent used is 3 times the total volume of the polyborazine precursor and the polysilazane precursor.

[0102] 2. Melt spinning

[0103] The solid multiphase precursor A is placed in a melt spinning device, and multiphase precursor fibers B with an average diameter of 16 μm are obtained through melt spinning.

[0104] 3. Partial oxidation treatment

[0105] The composite precursor fiber B was placed in an atmosphere sintering furnace, the reaction atmosphere was controlled to be dry air, the temperature was increased to 90°C at a heating rate of 10°C / min, and the temperature was kept for 30 minutes to obtain partially oxidized fiber C.

[0106] 4. Partial nitriding / carburizing treatment

[0107] After partially oxidized fiber C was prepared, the reaction atmosphere was controlled to be a mixture of ammonia and nitrogen, the temperature was increased to 400° C. at a heating rate of 10° C. / min, and the temperature was kept for 30 minutes to obtain partially nitrided / carbonized fiber D.

[0108] Among them, the volume ratio of ammonia to nitrogen is 1:10.

[0109] 5. Post-processing

[0110] After partially nitrided / carbonized fiber D was prepared, the reaction atmosphere was controlled to be nitrogen, the temperature was raised to 1200°C at a heating rate of 10°C / min, and the temperature was kept for 60 minutes to obtain a boron nitride fiber with a multilayer composite structure, namely, an absorbing boron nitride fiber.

[0111] The present embodiment also provides a wave-absorbing boron nitride fiber prepared by the above method, which comprises, from outside to inside, a wave-transmitting layer, a wave-absorbing layer, and a reflecting layer; the wave-transmitting layer has a thickness of 0.5 μm; the wave-absorbing layer has a thickness of 1 μm, and the reflecting layer has a thickness of 4 μm; the wave-absorbing boron nitride fiber has a relative dielectric constant of 3.6 and a dielectric loss of 3.4×10 -2 .

[0112] The specific specifications of the wave-absorbing boron nitride fibers obtained in Examples 1-3 are summarized in the following table:

[0113]

[0114] like Figure 1 The dielectric loss diagram of the absorbing boron nitride fiber is shown. In the diagram, the lower black line is the dielectric loss curve of the conventional boron nitride fiber in the prior art, and the upper red line is the dielectric loss curve of the absorbing boron nitride fiber of the present invention. It can be seen that the preparation method of the absorbing boron nitride fiber with adjustable dielectric properties of the present invention can effectively achieve cross-order-of-magnitude adjustment of the dielectric properties of the boron nitride fiber, and the absorbing boron nitride fiber exhibits certain dielectric loss performance.

[0115] The method for preparing a wave-absorbing boron nitride fiber with adjustable dielectric properties of the present invention comprises a wave-absorbing boron nitride fiber with adjustable dielectric properties, which comprises, from the outside to the inside, a wave-transmitting layer, a wave-absorbing layer, and a reflective layer. Taking a multiphase precursor fiber B with an average diameter of 16 μm prepared by melt spinning as an example, the wave-transmitting layer thickness of the finally prepared wave-absorbing boron nitride fiber is 0.5-4 μm, the wave-absorbing layer thickness is 0.5-2.5 μm, and the reflective layer thickness is 1-4 μm. The relative dielectric constant of the wave-absorbing boron nitride fiber is 3.5-7.5, and the dielectric loss is 9×10 -3 to 6.5×10 -2 ; It can effectively avoid the defects of poor bonding between surface coating and carrier fiber, easy delamination, impedance mismatch, and uneven thickness of surface coating in traditional absorbing materials; it can make boron nitride fiber have good electromagnetic wave absorption and reflection functions, while realizing cross-order magnitude adjustment of dielectric properties, effectively meeting the diversified needs of boron nitride fibers with different dielectric properties in the application field of electromagnetic absorbing materials, and further expanding the application field of boron nitride fibers.

[0116] Unless otherwise specified, all percentages used in the present invention are by mass.

[0117] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a microwave-absorbing boron nitride fiber with adjustable dielectric properties, characterized in that: The method comprises the following steps: activation treatment, melt spinning, partial oxidation treatment, partial nitridation / carbonization treatment, and post-treatment; The activation treatment method comprises dissolving a polyborazane precursor and a polysilazane precursor in a solvent to obtain a mixed precursor solution; subjecting the mixed precursor solution to ultrasonic treatment; while subjecting the mixed precursor solution to ultrasonic treatment, continuously introducing boron trichloride gas below the liquid surface of the mixed precursor solution to obtain an activation treatment solution; and removing the solvent from the activation treatment solution to obtain a solid multiphase precursor A. The melt spinning method comprises: performing melt spinning on a solid multiphase precursor A to obtain a multiphase precursor fiber B; The partial oxidation treatment method is to control the reaction atmosphere to be dry air, and to heat-treat the composite precursor fiber B at a temperature of 90-160° C. for 10-60 minutes to obtain a partially oxidized fiber C; In the partial oxidation treatment, the heating rate to 90-160°C is 1-10°C / min; The method of partial nitridation / carbonization treatment is to control the reaction atmosphere to be a mixture of ammonia and nitrogen, and to heat-treat the partially oxidized fiber C at a temperature of 400-600° C. for 10-60 minutes to obtain a partially nitrided / carbonized fiber D; In the partial nitriding / carbonizing treatment, the heating rate to 400-600°C is 1-10°C / min; the volume ratio of ammonia to nitrogen is 1:5-20; The post-treatment method is to control the reaction atmosphere to be nitrogen, and to heat-treat the partially nitrided / carbonized fiber D at a temperature of 1200° C. to obtain a wave-absorbing boron nitride fiber with adjustable dielectric properties; In the post-treatment, the heating rate to 1200° C. is 1-10° C. / min; and the heat treatment time at 1200° C. is 10-60 min.

2. The method for preparing the microwave-absorbing boron nitride fiber with adjustable dielectric properties according to claim 1, characterized in that: In the activation treatment, the mass ratio of the polyborazane precursor to the polysilazane precursor is 70-97:3-30; The volume of the solvent is at least 3 times the total volume of the polyborazane precursor and the polysilazane precursor.

3. The method for preparing the microwave-absorbing boron nitride fiber with adjustable dielectric properties according to claim 1, characterized in that: In the activation treatment, the ultrasonic frequency is 20-25kHz, the ultrasonic power is 450-550W, and the ultrasonic temperature is 50-60°C; The introduction rate of boron trichloride gas is 0.5-0.6L / min; The time for ultrasonic treatment and passing boron trichloride gas is 10-30 minutes.

4. The method for preparing the microwave-absorbing boron nitride fiber with adjustable dielectric properties according to claim 1, characterized in that: In the activation treatment, the polymer dispersibility index PDI of the solid multiphase precursor A obtained is between 2.2 and 4.

3.

5. The method for preparing the microwave-absorbing boron nitride fiber with adjustable dielectric properties according to claim 1, characterized in that: In the melt spinning, the average diameter of the complex phase precursor fiber B is 16-20 μm.

6. A microwave-absorbing boron nitride fiber with adjustable dielectric properties, characterized in that: The wave-absorbing boron nitride fiber with adjustable dielectric properties is prepared by the preparation method described in any one of claims 1 to 5, and comprises, from the outside to the inside, a wave-transmitting layer, a wave-absorbing layer, and a reflecting layer.

7. The microwave-absorbing boron nitride fiber with adjustable dielectric properties according to claim 6, characterized in that: The relative dielectric constant of the wave-absorbing boron nitride fiber with adjustable dielectric properties is 3.5-7.5, and the dielectric loss is 9×10 -3 to 6.5×10 -2 .

Citation Information

Patent Citations

  • Method for preparing BN-Si3N4 complex phase continuous ceramic fiber by composite organic precursor method

    CN107740205A

  • Boron content adjustable SiBN fiber preparation method and SiBN fiber

    CN110846742A